Metal–Organic Framework and Covalent–Organic Framework‐Based Aerogels: Synthesis, Functionality, and Applications - Gaofeng Shao; Xiaogu Huang; Xiaodong Shen; Changxia Li; Arne Thomas (Advanced Science)
Abstract Metal–organic frameworks (MOFs) and covalent–organic frameworks (COFs)‐based aerogels are garnering significant attention owing to their unique chemical and structural properties. These materials harmoniously combine the advantages of MOFs and COFs—such as high surface area, customizable porosity, and varied chemical functionality—with the lightweight and structured porosity characteristic of aerogels. This combination opens up new avenues for advanced applications in fields where material efficiency and enhanced functionality are critical. This review provides a comparative overview of the synthetic strategies utilized to produce pristine MOF/COF aerogels as well as MOF/COF‐based hybrid aerogels, which are functionalized with molecular precursors and nanoscale materials. The versatility of these aerogels positions them as promising candidates for addressing complex challenges in environmental remediation, energy storage and conversion, sustainable water‐energy technologies, and chemical separations. Furthermore, this study discusses the current challenges and future prospects related to the synthesis techniques and applications of MOF/COF aerogels.